Natality Detail File, 2006 (United States) ([Verlag nicht ermittelbar], 2009)
This collection provides information on live births in the United States during calendar year 2006. The natality data in these files are a component of the vital statistics collection effort maintained by the federal government. Birth data is limited to births occurring in the United States to United States residents and nonresidents. Births occurring to United States citizens outside of the United States are not included in this data collection. Part 1 contains data on births occurring within the United States, while Part 2 contains data on births occurring in the United States territories of Puerto Rico, the Virgin Islands, Guam, American Samoa, and the Commonwealth of the Northern Mariana Islands. Beginning in 2005, the United States file no longer includes geographic detail (e.g., mother's state of residence). Geographic variables for the United States Territories file include the territory and county in which the birth occurred and in which the mother resided. Other variables describe the place of delivery, who was in attendance, and medical and health data such as the method of delivery, prenatal care, tobacco and alcohol use during pregnancy, pregnancy history, medical risk factors, and infant health characteristics. Birth and fertility rates and other statistics related to this study can be found in the National Vital Statistics Report in the codebook documentation. Demographic variables include the child's sex and month and year of birth, the parent's age, race, and ethnicity, as well as the mother's marital status, education level, and residency status.